1996
DOI: 10.1111/j.1439-0507.1996.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungistatic and fungicidal activity of East African medicinal plants

Abstract: Extracts of the traditionally used medicinal plants Entada abyssinica (stem bark), Terminalia spinosa (young branches), Harrisonia abyssinica (roots), Ximenia caffra (roots), Azadirachta indica (stem bark), Zanha africana (stem bark) and Spilanthes mauritiana (roots and flowers) were investigated for fungistatic and fungicidal activity against Candida spp. and Aspergillus spp. by a microtitre serial dilution technique. Entada abyssinica, T. spinosa, X. caffra, A. indica, and Z. africana showed activity against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 10 publications
0
48
0
Order By: Relevance
“…Ximenia caffra, indicated for treatment of diabetes and sexually transmitted infections in this study, was shown elsewhere to possess antibacterial activity (Fabry et al, 1998). Fabry et al (1996) demonstrated the antifungal activity of Ximenia caffra. These findings validate the continued use of the plant species in treating sexually transmitted diseases, especially those caused by fungal and bacterial pathogens.…”
Section: Plants Used For Sexually Transmitted Diseasesmentioning
confidence: 99%
“…Ximenia caffra, indicated for treatment of diabetes and sexually transmitted infections in this study, was shown elsewhere to possess antibacterial activity (Fabry et al, 1998). Fabry et al (1996) demonstrated the antifungal activity of Ximenia caffra. These findings validate the continued use of the plant species in treating sexually transmitted diseases, especially those caused by fungal and bacterial pathogens.…”
Section: Plants Used For Sexually Transmitted Diseasesmentioning
confidence: 99%
“…Terpenoids, essential oils and some flavonoid compounds were reported to exhibit antifungal activities on some brown and white rot fungi (Cobb et al, 1968;Carll and Highley, 1999). Some of these compounds, such as saponin, were found to be fungistatic (Ahmad et al, 1998;Zehavi et al, 2008) while others, such as terpenoids, were found to be fungicidal (Fabry et al, 1996;Molina-Torres et al, 2004;Tripathi et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…All strains were cultured on Columbia Agar (BioMerieux, France) supplemented with 7 % sheep blood and cultured for 3 days at 37 8C under microaerophilic conditions with high humidity as detailed elsewhere. [21] Antimicrobial activity. Antimicrobial activity against H. pylori was determined by the agar dilution method recommended by the national committee for clinical laboratory (NCCL) standards.…”
Section: Methodsmentioning
confidence: 99%